ZmLBD2 a maize (Zea mays L.) lateral organ boundaries domain (LBD) transcription factor enhances drought tolerance in transgenic Arabidopsis thaliana - Jiao, Peng; Wei, Xiaotong; Jiang, Zhenzhong; Liu, Siyan; Guan, Shuyan; Ma, Yiyong (Frontiers in Plant Science, 2022)
Maize (Zea mays L.) is an annual gramineous herb and is among the world’s most important crop species. Drought is the main factor contributing to maize yield reduction. The lateral organ boundaries domain (LBD) proteins belong to a class of higher-plant-specific transcription factors. LBD proteins usually include the highly conserved lateral organ boundaries (LOB) domains that play essential roles in plant growth and response to biotic stresses. However, few studies have addressed the biological functions of LBD genes associated with maize response to drought. Here we cloned the ZmLBD2 gene from maize and described its role in combating drought. Investigating ZmLBD2 subcellular localization, we show that it localizes to the cell nucleus and can specifically bind with inverted repeats of “GCGGCG”. Under drought stress, Arabidopsis thaliana overexpressing ZmLBD2 performed better than the wild-type plants in terms of seed germination rates, root length, relative water content, fresh weight, chlorophyll content, proline content, and antioxidant enzyme content. Arabidopsis overexpressing ZmLBD2 contained less MDA, H2O2, and O2- than the wild-type plants. Our protein-protein interaction results indicate an interaction between the ZmLBD2 and ZmIAA5 genes. In conclusion, the ZmLBD2 gene positively regulates H2O2 homeostasis in plants, strengthening drought resistance.